The seventeenth-century modernisation of the town hall of ‘s-Hertogenbosch (Bulletin KNOB, 2007)
In this article the 17th-century modernisation of the town hall of ' s -Hertogenbosch is explored. The central question is how fundamental the transformation of the medieval town hall was. The major part of the conversion was the new natural stone facade. This façade, designed by Pieter Minne and Dirk van der Lith, follows a scheme going back to the type of the Italian villa. It is not clear whether the architects actually reverted to the Italian tracts.For practical reasons the proportions of the facade deviate from the Standard rules. but nevertheless the facade is not at all provincial in character. Among other things, this appears from a comparable and more recent design for a town hall by Philip Vingboons. The modernisation was not limited to a cosmetic intervention.As opposed to other seventeenth-century modernisations of town halls, in 's-Hertogenbosch the entire internal disposition was changed drastically. A clustering of medieval dwellings was thereby converted into one single building with a rational layout. Although the floor plan is dependent on the old situation, the town hall has a successful disposition, going back to the villa type, just as the facade.The fact that the new layout of the town hall was not just an unfortunate compromise to the medieval situation, follows from the similar layout of the more recent town hall of Enkhuizen, where earlier buildings did not play a part. Consequently, it can be stated that the town hall of 's-Hertogenbosch is not only characterised by the renovated façade, but also by its modern typology.